VD_FINDINFO AP / 2011 / 79 vom 27. Mai 2010 - VD Tribunal cantonal (2010)
CONTRAT D'ENTREPRISE, DROIT À LA RÉSOLUTION DU CONTRAT, RÉSILIATION, PROLONGATION DU DÉLAI, INDEMNITÉEN GÉNÉRAL | 366 CO, 377 CO, 3 CPC, 444 CPC, 447 CPC, 451 ch. 4 CPC, 457 CPC, 405 al. 1 CPC (CH)